2021
DOI: 10.5812/aapm.112225
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Hypogastric Block for the Treatment of Chronic Pelvic Pain

Abstract: Context: Pelvic pain is described as pain originating from the visceral or somatic system localizing to the pelvis, the anterior abdominal wall at the level of or below the umbilicus, lumbosacral back in either men or women. Evidence Acquisition: Narrative review. Results: Chronic pelvic pain can be a complex disorder that may involve multiple systems such as urogynecological, gastrointestinal, neuromusculoskeletal, and psychosocial systems. The etiopathogenesis for chronic pain remains unknown for many patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…In addition to these publications, there are some studies regarding the efficacy of IHP blockade as a new target to relieve pain from the lower pelvic organs and genitalia [43]. Schultz [44] reported a novel technique using a fluoroscopy-guided transsacral approach towards the medial interior edge of the ventral sacral foramen to reach the IHP.…”
Section: Patient With Neuropathic Painmentioning
confidence: 99%
“…In addition to these publications, there are some studies regarding the efficacy of IHP blockade as a new target to relieve pain from the lower pelvic organs and genitalia [43]. Schultz [44] reported a novel technique using a fluoroscopy-guided transsacral approach towards the medial interior edge of the ventral sacral foramen to reach the IHP.…”
Section: Patient With Neuropathic Painmentioning
confidence: 99%
“…While data on chronic abdominal pain remains limited, a cross-sectional survey reported that 25% of the adult population admitted to living with abdominal pain. It reported no substantial difference in prevalence when factoring in age and ethnicity but did note a substantial increase in prevalence among women compared to men ( 11 ), partly possibly due to inclusion of pelvic pain ( 12 - 14 )…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…When chronic abdominal pain is concerned, the etiologies vary, and so will the possible treatments ( 22 ). When non-syndromatic pain is diagnosed, different approaches are possible; these include conservative treatments, oral non-opioid pharmacotherapy, opioid-based therapy, continuous infusions, and interventional approaches ( 14 , 23 - 30 ). Syndromatic pain, including IBD and IBS may require specialized therapy.…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…Interventional procedures vary by complexity and invasiveness, including trigger point injections, epidural steroid injections, sympathetic nerve blocks, radiofrequency ablation, cryoneuroablation, intrathecal drug delivery systems, and spinal cord stimulators, and deep brain stimulation (40)(41)(42)(43)(44)(45)(46). Although interventional therapies have associated risks, such as infection, dural puncture, spinal cord trauma, or nerve injury, the significant improvement in quality of life for certain patients makes them attractive treatment options, particularly in those who do not respond well to topical or oral analgesic agents (47-53).…”
Section: Interventional Pain Managementmentioning
confidence: 99%